SURVEI POTENSI PASIR KUARSA DI DAERAH KETAPANG PROPINSI KALIMANTAN BARAT - Prayogo, Teguh; Budiman, Bayu (Jurnal Sains dan Teknologi Indonesia, 2009)
Ketapang area is one of lower part or southern sub-province of West Kalimanatan Province, which is located geographically between 108o40’ and 111o20’ in Longitude and between 0o20’ and 3o04’ in Latitude. This area has various of industrial mineral resources, for example quartz sand. Quartz sand or also calledwith white sand is the reasult of rock weathering that contents main mineral, such as quartz, and felsdpar. Then, the result of weathering is cleaned and transported by water or wind and deposited in the stream side, lake or sea. In this paper will bedescribed concerning to locations, characteristics, and usages of quratz sand in Ketapang area, West Kalimantan Province. Based on chemical or laboratory analysis and interpretation, the quartz sands can be used as glass industry, cement industry material, and moulding industry.